Effect of the CuAl(2)O(4) and CuAlO(2) Phases in Catalytic Wet Air Oxidation of ETBE and TAME using CuO/γ‐Al(2)O(3) catalysts - Sánchez‐Trinidad, Cecilia (ChemistryOpen, 2019)
This paper studies Cu/Al(2)O(3) catalysts, synthesized in two ways: copper deposit in the synthesis of alumina (sol gel) and incipient impregnation stabilized at 400 °C. The materials were characterized by X‐ray diffraction studies, nitrogen physisorption, temperature programmed reduction of H(2), dehydration of isopropanol, scanning electronic microscopy, transmission electronic microscopy, which were evaluated in the liquid phase oxidation reaction of ethyl tert‐butyl ether and tert‐amyl methyl ether. The formation of CuAl(2)O(4) and CuAlO(2) in the samples synthesized by sol gel, led to a modification of the texture, thus resulting in an expansion of the specific area of the materials. CuAl(2)O(4) and CuAlO(2) have been identified by DRX from a content of 10 % Copper, the first showed the highest intensity with this technique. In the same way, these species favor the presence of Lewis acid sites; this is reflected in the materials with (Di‐isopropyl Ether) DIPE of 96.7 % and 91.1 % for the samples SAlCu5 and SAlCu15 respectively. The catalytic activity of the materials prepared by sol gel is in the function of the number of surface acid sites, the smaller particle size of the Cu and the surface of the contact, in the case of the ETBE meanwhile for TAME the activity was based mainly on the strength of the present acid sites. With impregnated materials, the activity is attributed to the smaller particle size of the Cu and the greater strength of the surface acid sites in the solid. The formation of spinel species inhibits the leaching phenomenon in the reaction milieu.